Models for cooperative games with fuzzy relations among the agents : fuzzy communication, proximity relation and fuzzy permission - Jiménez-Losada, Andrés (Springer, 2017)
This book offers a comprehensive introduction to cooperative game theory and a practice-oriented reference guide to new models and tools for studying bilateral fuzzy relations among several agents or players. It introduces the reader to several fuzzy models, each of which is first analyzed in the context of classical games (crisp games) and subsequently in the context of fuzzy games. Special emphasis is given to the value of Shapley, which is presented for the first time in the context of fuzzy games. Students and researchers will find here a self-contained reference guide to cooperative fuzzy games, characterized by a wealth of examples, descriptions of a wide range of possible situations, step-by-step explanations of the basic mathematical concepts involved, and easy-to-follow information on axioms and properties.
Keywords: Cooperative games (Mathematics); Fuzzy mathematics.; elektronické knihy; electronic books